The Application of Living and Recognized Customary Law as a Material Source of Law in Criminal Judicial Practice Based on Article 2 Paragraph (1) of the 2023 Criminal Code (KUHP) - Ibnu Daisaly Aziz; Abraham Ferry Rosando (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The recognition of living law as a material legal source in Article 2 paragraph (1) of the 2023 Criminal Code (KUHP) marks a significant paradigm shift in Indonesia’s criminal law system. This study aims to analyze the application of living and recognized customary law in judicial practice. Using a normative legal research method with statutory, conceptual, comparative, and case approaches, the results show that the application of customary law can function positively (as a basis for punishment) and negatively (as a ground for abolition or mitigation of punishment) if it meets the cumulative criteria in Article 2 paragraph (2) and is verified through Government Regulation No. 55 of 2025. In practice, the mechanism begins from the investigation stage to execution. However, it still faces various challenges, including multiple interpretations, regional disparities, the paradox of formalization, and the potential for judicial tyranny. Therefore, strengthening through more technical regulations, capacity building for law enforcement officials, and active participation of indigenous communities is urgently needed to realize restorative justice with legal certainty.